Pengembangan Modul Fisika Berbasis Model Pembelajaran REACT Pada Materi Gelombang Bunyi Untuk Meningkatkan Kemampuan Memahami Konsep Siswa Kelas XI SMA - Rury Septyowaty; Azizahwati; Muhammad Syafii (Postgraduate, University of Mataram, 2023)
This study aims to find out how to apply the guided inquiry learning model to improve the ability of psychomotor skills and learning interests of grade X students of TKPI SMKN Fisheries Riau Province. This type of research is a Classroom Action Research Physics model of Kemmis and Mc Taggart which consists of 2 cycles, where each cycle includes stages of planning, action and observation, as well as reflection. In cycle I, students learn about temperature and heat, and cycle II, students learn about dynamic electricity. Data collection techniques include observation sheets of teacher and student activities, performance tests, and interest questionnaires. The subjects of this study were grade X TKPI students, totaling 16 male students.The data were analyzed in descriptive, qualitative and quantitative manners. Observations are made by peers to observe the implementation of teacher and student activities in accordance with the learning steps in RPP. Performance tests are carried out at the end of each cycle. Filling out the learning interest questionnaire at the end of cycle I and cycle II. The results of research on how to apply the guided inquiry method are by the way the teacher makes an orientation of a problem that will be formulated by students to attract students' attention, then involves students directly in making hypotheses, conducting experiments, analyzing data to train students' psychomotor skills, so that students are happy in making conclusions for the theories they get. The research data showed that teacher activities and student activities were carried out according to the RPP, with very good criteria, students' psychomotor skills at the level of imitation, manipulation and precision trained in each learning meeting, increased by 25%, from 69% classical completeness to 94%, and students' interest in learning physics after applying the guided inquiry learning model increased by 16% from 65% with sufficient criteria to 81% with very good criteria. Students have a feeling of pleasure being actively involved in the learning process, so they are interested and more attentive to learning.